2009
DOI: 10.1007/s10067-009-1213-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of splinting and splinting plus low-level laser therapy in idiopathic carpal tunnel syndrome

Abstract: This study aimed to compare the short-term efficacy of splinting (S) and splinting plus low-level laser therapy (SLLLT) in mild or moderate idiopathic carpal tunnel syndrome (CTS) with a prospective, randomized controlled study. The patients with unilateral, mild, or moderate idiopathic CTS who experienced symptoms over 3 months were included in the study. The SLLLT group received ten sessions of laser therapy and splinting while S group was given only splints. The patients were evaluated at the baseline and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 25 publications
1
28
0
1
Order By: Relevance
“…This contention is same as that in the past research 17) . Applied to clinical treatments of CTS, LLLT was more effective than other conservative treatments 18,19) . It was apparent based on their results as well as ours, especially for the improvement in symptom severity and neurological signs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This contention is same as that in the past research 17) . Applied to clinical treatments of CTS, LLLT was more effective than other conservative treatments 18,19) . It was apparent based on their results as well as ours, especially for the improvement in symptom severity and neurological signs.…”
Section: Discussionmentioning
confidence: 99%
“…The velocity of neural conduction also showed statistical significance after the treatment (p<0.05). Some studies found that LLLT performed better than other conservative treatments in reducing neurological signs and nerve conduction velocity 18,19) . Although the effect on neural tissues generated by LLLT is not clear yet, the NCS of CTS were found to be related to the degree of severity of the symptoms in our research.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 In a recent prospective, randomized, placebo-controlled trial Evcik, et al reported positive effects on hand and pinch grip strengths after low-level laser therapy. 28 Beneficial effects of the combination of laser therapy with other methods as night orthopedic splint 25 or magnetic stimulation 29 were also reported.…”
Section: Discussionmentioning
confidence: 99%
“…The dose generally used is 8-10 J/cm 2 with a wavelength ranging from 830-904 nm 39 . This low-level laser therapy is applied through a specific probe at different points (usually three) in the wrist where the median nerve travels superficially 40 . The duration of application at each point is 90 seconds 40 .…”
Section: Low-level Laser Therapymentioning
confidence: 99%
“…This low-level laser therapy is applied through a specific probe at different points (usually three) in the wrist where the median nerve travels superficially 40 . The duration of application at each point is 90 seconds 40 . The purpose of the treatment is to reduce the inflammatory process and edema, but some authors have used the laser as a tool to stimulate points used in acupuncture with the aim of improving associated pain 41 .…”
Section: Low-level Laser Therapymentioning
confidence: 99%